Restriction of Dietary Advanced Glycation End Products Induces a Differential Plasma Metabolome and Lipidome Profile. Issue 23 (20th October 2021) - Berdún, Rebeca; Jové, Mariona; Sol, Joaquim; Cai, Weijing; He, John C.; Rodriguez‐Mortera, Reyna; Martin‐Garí, Meritxell; Pamplona, Reinald; Uribarri, Jaime; Portero‐Otin, Manuel
Abstract : Scope: Diets with low content in advanced glycation end products (AGEs) lead to beneficial properties in highly prevalent age‐related diseases. To shed light on the mechanisms behind, the changes induced by a low AGE dietary intervention in the circulating metabolome are analyzed. Methods and Results: To this end, 20 non‐diabetic patients undergoing peritoneal dialysis are randomized to continue their usual diet or to one with a low content of AGEs for 1 month. Then, plasmatic metabolome and lipidomes are analyzed by liquid‐chromatography coupled to mass spectrometry. The levels of defined AGE structures are also quantified by ELISA and by mass‐spectrometry. The results show that the low AGE diet impinged significant changes in circulating metabolomes (166 molecules) and lipidomes (91 lipids). Metabolic targets of low‐AGE intake include sphingolipid, ether‐lipids, and glycerophospholipid metabolism. Further, it reproduces some of the plasma characteristics of healthy aging. Conclusion: The finding of common pathways induced by low‐AGE diets with previous metabolic traits implicated in aging, insulin resistance, and obesity suggest the usefulness of the chosen approach and supports the potential extension of this study to other populations. Abstract : A diet with a low‐advanced glycation end product content induces specific metabolomics and lipidomic changes in plasma. These changes can be related to several pathways, related to lípid pathways involved in inflammation, and age‐related changes. Overall, they support diet‐induced enhancements in oxidative stress resilience.